2004
DOI: 10.1007/s00774-004-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simvastatin on serum cytokine levels and bone metabolism in postmenopausal subjects: negative correlation between TNF-α and anabolic bone parameters

Abstract: In this prospective study, we aimed to evaluate the effect of simvastatin on bone metabolism and the correlation between changes in bone turnover parameters and serum cytokine levels. For this purpose, 38 postmenopausal subjects with hypercholesterolemia (>240 mg/dl), not on osteoporosis treatment, were studied. Simvastatin was started at a dose of 20 mg daily and continued for 3 months. Six patients were excluded from the study during the follow-up period. Pre- and post-treatment samples were analyzed for bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the present experiments, simvastatin‐treated animals (30 mg/kg) show enhanced TAP serum values on day 11 compared with the other groups. Several in vivo studies have demonstrated that oral and topical statins improved TAP 48,49 and bone‐specific alkaline phosphatase levels 50 . Some in vitro studies also showed greater expression of these enzymes in bone cell cultures exposed to simvastatin 10 …”
Section: Discussionmentioning
confidence: 99%
“…In the present experiments, simvastatin‐treated animals (30 mg/kg) show enhanced TAP serum values on day 11 compared with the other groups. Several in vivo studies have demonstrated that oral and topical statins improved TAP 48,49 and bone‐specific alkaline phosphatase levels 50 . Some in vitro studies also showed greater expression of these enzymes in bone cell cultures exposed to simvastatin 10 …”
Section: Discussionmentioning
confidence: 99%
“…Vascular invasion is a prerequisite for calcification during endochondral bone formation (Gerber et al, 1999); thus, the well established proangiogenic effect of statins might increase bone formation. Statins may also affect bone formation indirectly by inhibiting inflammation that is responsible for an imbalance in bone metabolism by favoring bone resorption (Tikiz et al, 2004;Tanaka et al, 2005).). It is noteworthy that Yavuz et al (2009) have described an interesting relationship between statins and the vitamin D physiology that might represent a new pleiotropic effect of this class of drugs with great bone anabolic potential.…”
Section: F Statins and Bonementioning
confidence: 99%
“…Statins, drugs widely used for lowering serum cholesterol, have been found to enhance new bone formation (22)(23)(24) and reduce risk of fractures (25,26). Postmenopausal women were studied to determine the relation between statin use and BMD (27).…”
Section: Dietary Sources Of Bmp-2 Stimulants: Flavonoids and Statinsmentioning
confidence: 99%